Pengaruh Indeks Massa Tubuh Dengan Kejadian Hipotermi Pada Pasien Anestesi Spinal - M.Rossy Rakasiwi; Weni Hastusi; Ghea Nurprastina (Jurnal Sains dan Kesehatan, 2021)
Body Mass Index (BMI) is the most commonly used and practical indicator for measuring levels of overweight and obesity in adults. to determine the relationship between body mass index and the incidence of hypothermia in post-spinal anesthesia patients at the Central Surgical Installation (IBS) of Ibnu Sina Hospital, Gresik Regency. The research design used was a cross-sectional study with a population of 100 people. The sample used in this study was purposive sampling with 80. Results: the majority of respondents had a BMI of 18.5-25.0 (normal ) (88.8%). The incidence of hypothermia in the majority of respondents was body temperature ≤36°C (hypothermia) (77.5%) and the results of Chi-Square Tests showed a p-value <0.05, namely p-value = 0.001, so it can be concluded that there is a significant relationship Between the relationship between Body Mass Index and the incidence of hypothermia in patients after spinal anesthesia at Ibnu Sina Regional Hospital. Conclusion: based on research that there is a relationship between Body Mass Index and the incidence of hypothermia in patients after spinal anesthesia at Ibnu Sina Regional Hospital.